A comprehensive mapping of stress system interactions with pain and their contribution to chronification of musculoskeletal pain: Protocol of the STRAIN study - Moerkerke, Matthijs; Vyverman, Joren; De Baere, Robrecht; Clement, Patricia; Smeets, Tom; Coppieters, Iris; Timmers, Inge; Van Oosterwijck, Jessica (PloS one, 2025)
Stress is suggested to be an important factor contributing to the development and persistence of musculoskeletal pain. Although stress and pain interactions are well known, it remains largely unclear how (dys)function of the major stress systems (i.e., the autonomic nervous system and the hypothalamic-pituitary-adrenal axis) contributes to pain extent and duration, and what the underlying mechanisms are. A comprehensive characterization of the stress systems and their interactions with pain is needed to better understand how stress confers vulnerability for persistent pain. The primary aim of this study is to characterize stress system (dys)functioning (i.e., including basal levels, reactivity and recovery to acute stress, and chronic stress levels) in musculoskeletal pain groups with varying pain duration and extent, and to investigate the interaction between stress and pain at the psychosocial, (psycho)physiological and neural level. The secondary aim is to define the contribution of stress to pain trajectories, including chronification and recovery. A study with a cross-sectional and a longitudinal arm will be conducted in musculoskeletal pain groups with varying pain characteristics, including chronic widespread pain (fibromyalgia), chronic and subacute localized pain (low back pain), and pain-free controls (n = 35/group). To characterize pain trajectories (recovery/persisting), localized pain groups will be reassessed after six months. Stress and pain characteristics and functionality will be assessed using questionnaires, autonomic measures (alpha-amylase, blood pressure, heart rate, respiratory rate, skin conductance and skin temperature), hormonal concentrations (cortisol and oxytocin), quantitative sensory testing (pain thresholds, pain tolerances, conditioned pain modulation and temporal summation of pain), and magnetic resonance imaging (brain structure and function). This study will provide crucial insights in the role of stress in the extent of pain symptomatology and in conferring risk for pain chronicity. Additionally, it will shed light on the underlying mechanisms of stress and pain interactions. Trial registration: ClinicalTrials.gov (NCT06892977).